An unusual type of accessory pathway in tricuspid atresia - Prabhu, Mukund A. (J Cardiol Cases, 2016)
The occurrence of pre-excitation in tricuspid atresia (TA) is slightly more common than that in normal children. The accessory pathway (AP), when it occurs in the setting of congenital atrioventricular valvar disease, is usually ipsilateral to the side of the abnormal valve. This report describes a patient with TA who had pre-excitation due to a left-sided AP that masked and modified the typical electrocardiographic features. The electrophysiological study confirmed an epicardial left posterior AP that was successfully ablated with radiofrequency energy, through the coronary sinus. Left-sided APs including epicardial ones may rarely be seen in TA and can potentially cause difficulties due to lack of vascular access to the heart after the Fontan surgery if arrhythmias occur. They are amenable to successful radiofrequency ablation and need to be dressed prior to Fontan surgery. <Learning objective: Pre-excitation may become manifest during follow-up even if minimal at initial presentation. Accessory pathways may occur in the left side of the heart in tricuspid atresia, in contrast to the usual notion that APs occur ipsilateral to the side of the abnormal valve. Electrophysiological study may be useful prior to Fontan-type procedures as this helps in identifying and to prognosticate pre-excitation so that ablation of the pathway can be performed prior to the Fontan procedure.>